Paradox of Becoming Wealthy in J. Blakeson's I Care a Lot - Az Zahra Sekar Ayu Arumbinang; Melania Shinta Harendika (Universitas Brawijaya, 2020)
The American dream is a national ethos that originated in the United States of America and is widely known and believed by people all over the world. In order to create their American dream, particularly the dream of becoming wealthy, traditional American values are required. In the midst of fulfilling one American dream, a person may unknowingly create a paradox by doing things that are believed to be true but are ironically incorrect. The paradox of becoming wealthy can be found in a person's endeavor by following traditional American principles or inside its actual profession by engaging in a criminal action, sometimes known as a crime. The paradox appeared in the movie I Care a Lot by J. Blakeson which tells the story of Marla Grayson, a court-appointed guardian for the elderly who uses her wards as a weapon to achieve her American goal of being wealthy, and Dr. Karen Amos, a physician who sells personal information about her patients in order to get rich. Both committed a crime and transgressed conventional American principles of material prosperity and hard effort.